EKSISTENSI MANAJEMEN LABA DAN NILAI TUKAR RUPIAH (KURS) SEBAGAI KATALISATOR REAKSI INVESTOR PASAR MODAL PADA PERUSAHAAN FARMASI YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2015-2019 - Yusuf, Fitria Melynsyah; Hippy, Moh. Zubair (JSAP : Journal Syariah and Accounting Public, 2020)
This study aims to determine the partial or simultaneous effect of earnings management and the Rupiah exchange rate (Exchange rate) on the market reaction of pharmaceutical companies listed on the Indonesia Stock Exchange for the 2015-2019 period. This research is a quantitative research. The source of data in this study is secondary data in the form of annual financial statements of companies listed on the IDX. Then the stock price is obtained from the yahoo finance site. The sampling method is purposive sampling. The data analysis technique used is multiple regression analysis of panel data constructs. The results of this study indicate that partially earnings management has no significant effect on capital market reactions while the Rupiah exchange rate (exchange rate) has a significant effect on capital market reactions. Simultaneously, earnings management and the exchange rate of the rupiah (exchange rate) have a significant effect on the reaction of the capital market